Ethnoknowledge about stingless bees (Anthophila, Apidae: Meliponini) by community residents in Cabeceiras do Piauí, Piauí, Brazil - Batista, Márcio Luciano Pereira; Silva, Paulo Roberto Ramalho; Costa Neto, Eraldo Medeiros; Oliveira, Favízia Freitas de; Barros, Roseli Farias Melo de (ACTA Apicola Brasilica, 2020)
The accuracy of obtaining knowledge of the diversity of native bees in a given location and their interrelationships with the ecosystem are numerous, after all, besides being the biggest pollinators and responsible for the development of existing plants in the environment, they are also stand out for their economic and socio-cultural value. The objective was to record the ethnoknowledge about stingless bees by the residents of the José Gomes community, in the municipality of Cabeceiras do Piauí, Piauí. The data were collected through semi-structured interviews applied to 43 local actors, 39 men and four women. The meliponines were captured through entomological net and containers, and sent for identification. 124 specimens were collected, distributed in six genera and 13 species of stingless bees. Of the sampled species, the most abundant were Scaptotrigona sp. (n = 25), Trigona sp. (n = 17), Tetragona sp. (n = 14), Trigona spinipes (n = 13) and Partamona ailyae (n = 10). The Shannon-Wiener index (H ') was used to estimate the diversity of stingless bees, which was H ’= 1.02. It was found that the residents perceive and recognize the diversity of meliponines existing in the studied area, however it is necessary to establish greater disclosure about the importance of the role of these insects for the conservation of the ecosystem, improved through an intensified environmental education, mainly regarding the conservation of stingless bees and melitophilous plants.